2017
DOI: 10.1590/0103-8478cr20151563
|View full text |Cite
|
Sign up to set email alerts
|

The optimal number of partial least squares components in genomic selection for pork pH

Abstract: Número ótimo de componentes nos quadrados mínimos parciais aplicados à seleção genômica para pH da carne suína

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is important to highlight that the larger the data set, the more computational resources are required under the MT-PLS model because in order to select the optimal hyperparameters (number of principal components), an inner (nested) cross-validation needs to be implemented to select the optimal number of principal components. However, Silveira et al (2017) conducted research for selecting the optimal number of principal components in the context of UT-PLS using nested cross-validation as we did and using the degree-of-freedom (DoF) method and they reported that both approaches found the same optimal number of components. This option for selecting the optimal number of principal components should be explored in the context of MT-PLS since significant computational resources can be saved for implementing the MT-PLS method.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that the larger the data set, the more computational resources are required under the MT-PLS model because in order to select the optimal hyperparameters (number of principal components), an inner (nested) cross-validation needs to be implemented to select the optimal number of principal components. However, Silveira et al (2017) conducted research for selecting the optimal number of principal components in the context of UT-PLS using nested cross-validation as we did and using the degree-of-freedom (DoF) method and they reported that both approaches found the same optimal number of components. This option for selecting the optimal number of principal components should be explored in the context of MT-PLS since significant computational resources can be saved for implementing the MT-PLS method.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the applications in biometrics, environmental and agricultural data of regression methods based on dimensionality reduction are observed in the genomic selection (Azevedo et al, 2013a;Azevedo et al, 2013b;Azevedo et al, 2014;Azevedo et al, 2015;Silveira et al, 2017), gene expression (Nascimento et al, 2017), spectroscopy analysis NIR (Near Infrared) (Morgano et al, 2005;Teófilo et al, 2009), sensory data (Westad, 2005), climatic data (Lim et al, 2015) and process control data (Han et al, 2003), among others. However, dimensionality reduction methods can be applied whenever multicollinearity and high dimensionality are present, and the the study is aimed at regression.…”
Section: Introductionmentioning
confidence: 99%